2010
DOI: 10.1016/j.ccr.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

PML/RARA Oxidation and Arsenic Binding Initiate the Antileukemia Response of As2O3

Abstract: As(2)O(3) cures acute promyelocytic leukemia (APL) by initiating PML/RARA oncoprotein degradation, through sumoylation of its PML moiety. However, how As(2)O(3) initiates PML sumoylation has remained largely unexplained. As(2)O(3) binds vicinal cysteines and increases reactive oxygen species (ROS) production. We demonstrate that upon As(2)O(3) exposure, PML undergoes ROS-initiated intermolecular disulfide formation and binds arsenic directly. Disulfide-linked PML or PML/RARA multimers form nuclear matrix-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
326
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(339 citation statements)
references
References 49 publications
11
326
0
2
Order By: Relevance
“…Indeed, PML --RARa represents the direct pharmaceutical target of two effective agents for APL, ATRA and ATO (Figure 1a). Arsenic binds to the RBCC domain of PML moiety, 24,25 whereas ATRA targets the RARa moiety of PML --RARa. Both the agents can induce the degradation of PML --RARa, 26 --29 which probably accounts for their curable effects.…”
Section: Leukemogenesis Of Apl and Mechanisms Underlying Effect Of Atmentioning
confidence: 99%
“…Indeed, PML --RARa represents the direct pharmaceutical target of two effective agents for APL, ATRA and ATO (Figure 1a). Arsenic binds to the RBCC domain of PML moiety, 24,25 whereas ATRA targets the RARa moiety of PML --RARa. Both the agents can induce the degradation of PML --RARa, 26 --29 which probably accounts for their curable effects.…”
Section: Leukemogenesis Of Apl and Mechanisms Underlying Effect Of Atmentioning
confidence: 99%
“…APL is caused by the expression of PML/RARA, a protein resulting from the fusion of PML, a redox-sensing protein that organizes nuclear domains, with RARA (43)(44)(45)(46)(47). APL has drawn much attention because of its exquisite sensitivity to RA, which induces APL cell differentiation in vivo or ex vivo.…”
Section: Can Targeted Therapies Really Work In Patients?mentioning
confidence: 99%
“…8 Indeed, the exquisite sensitivity of APL to ATO treatment has been recently demonstrated to be mediated by PML-RARa oxidation and subsequent degradation in an ROS-dependent process. 9 Interestingly, Weber et al 10 demonstrated that p0 cells that lack mitochondrial respiratory chain (MRC) activity are insensitive to a-TOS toxicity. However, few data are available regarding the early molecular events underlying this action.…”
Section: Introductionmentioning
confidence: 99%